1999
DOI: 10.3171/jns.1999.91.1.0035
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and radiotherapy compared with gamma knife radiosurgery in the treatment of solitary single cerebral metastases of small diameter

Abstract: Radiosurgery alone can result in local tumor control rates as good as those for surgery plus WBRT in selected patients. Radiosurgery should not be routinely combined with radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(126 citation statements)
references
References 38 publications
5
115
1
5
Order By: Relevance
“…Bindal et al 21 noted a significant survival benefit for patients treated with surgical resection compared with SRS, while Auchter et al 22 concluded that SRS was as efficacious as resection. In yet a third study, Muacevic et al 23 found no marked difference in survival. Clearly, further studies are warranted regarding the use of SRS in general and in ovarian carcinoma patients with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Bindal et al 21 noted a significant survival benefit for patients treated with surgical resection compared with SRS, while Auchter et al 22 concluded that SRS was as efficacious as resection. In yet a third study, Muacevic et al 23 found no marked difference in survival. Clearly, further studies are warranted regarding the use of SRS in general and in ovarian carcinoma patients with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been no randomized clinical trials comparing surgery plus SRS or surgery versus SRS, retrospective analyses have shown similar survival improvement between SRS and surgery alone, and the decision to perform surgery or SRS should be made on a case-by-case basis, accounting for symptomaticity, tumor site, size, and surgeon's preference [11,[44][45][46]. O'Neill and colleagues have shown that SRS is more effective at preventing local recurrences (0 %, 0/26) than surgery (27 %, 19/74).…”
Section: Surgery and Stereotactic Radiosurgerymentioning
confidence: 99%
“…Another advantage of surgical resection is the pathologic confi rmation of the malignant nature of the lesion. Postoperative radiotherapy has demonstrated a decrease in the recurrence of brain metastases, a decrease in the mortality due to neurological deterioration and a delay in neurologic clinical deterioration [2,3].Radiosurgery has emerged as a non-invasive option to treat patients with 1-3 brain metastases, providing similar local control rates to surgery [4][5][6]. However, no randomised trial has compared the two approaches.…”
mentioning
confidence: 99%
“…Radiosurgery has emerged as a non-invasive option to treat patients with 1-3 brain metastases, providing similar local control rates to surgery [4][5][6]. However, no randomised trial has compared the two approaches.…”
mentioning
confidence: 99%